Erect Penile Dimensions in a Cohort of 778 Middle Eastern Men: Establishment of a Nomogram. (1st June 2015) - Habous, Mohamad; Tealab, Alaa; Williamson, Ben; Binsaleh, Saleh; El Dawy, Sherif; Mahmoud, Saad; Abdelwahab, Osama; Nassar, Mohammed; Mulhall, John P.; Veale, David; Muir, Gordon
Abstract: Introduction: Accurate data regarding the size of the erect penis are of great importance to several disciplines working with male patients, but little high-quality research exists on the subject, particularly in different ethnic groups and for erect penis size. Aim: The aim of this study was to create a nomogram of erect penile dimensions in a large sample of Middle Eastern men. Methods: A retrospective cohort study of 778 men (mean age 43.7; range 20–82) attending urological outpatient clinics in Saudi Arabia was conducted. Exclusion criteria were age under 18 years, a presenting complaint of small or short penis, Peyronie's disease or complaint of congenital curvature, clinical hypogonadism, and previous penile surgery or trauma. Main Outcome Measures: Three erect penile dimensions following induction of erection using intracavernosal injection of Quadrimix. Results: Mean patient body mass index (BMI) was 29.09 (standard deviation [SD] 5.76). The mean suprapubic skin-to-penile tip erect length was 12.53 cm (SD 1.93); the mean erect length from the symphysis pubis to the penile tip was 14.34 cm (SD 1.86); and the mean erect shaft circumference was 11.50 cm (SD 1.74). A nomogram was constructed and statistical analysis performed, demonstrating a weak negative correlation between BMI and erect penile length measured from the suprapubic skin (r = −0.283, P < 0.000) but not from bone to tip, and a weak negative correlation between age and both erect penile length measurements (skin to tip r = −0.177, P < 0.0005; bone to tip r = −0.099, P = 0.006). Conclusion: A nomogram for Middle Eastern men can be used as a standard when advising men with small penis anxiety. The importance of measuring erect size and allowing for infra-pubic fat interference in measurement is emphasized. We envisage that this tool can be used to educate and reassure concerned men about the size of their penises.